2011
DOI: 10.1089/pho.2010.2784
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Swimming Exercise Intensities on Bone Tissue Composition in Mice: A Raman Spectroscopy Study

Abstract: Raman technique associated with PCA statistics showed that intense swimming exercise may affect bone mineralization and remodeling in a mouse model of training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
1
5
0
1
Order By: Relevance
“…A previous study reported that high-intensity treadmill running increased crystallinity and the carbonate-to-phosphate ratio of the subchondral trabecular tibia while decreasing the mineral-to-matrix ratio of the subchondral trabecular tibia in rats [ 19 ]. Another study reported that low- or high-intensity swimming slightly increased the carbonate-to-phosphate ratio in the mid-diaphysis femur [ 17 ]. However, low or moderate treadmill running does not affect the chemical properties of the subchondral trabecular tibia [ 19 ] or mid-diaphysis femur [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported that high-intensity treadmill running increased crystallinity and the carbonate-to-phosphate ratio of the subchondral trabecular tibia while decreasing the mineral-to-matrix ratio of the subchondral trabecular tibia in rats [ 19 ]. Another study reported that low- or high-intensity swimming slightly increased the carbonate-to-phosphate ratio in the mid-diaphysis femur [ 17 ]. However, low or moderate treadmill running does not affect the chemical properties of the subchondral trabecular tibia [ 19 ] or mid-diaphysis femur [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of these chemical properties has led to the development of more detailed assessments of bone strength and fracture risk. Although the effects of exercise on bone chemical properties have been studied using Raman spectroscopy [ 17 , 19 - 21 ], the effects of food restriction under both sedentary and exercise conditions have received little attention. Possibly, bone chemical properties are altered by decreased intake of bone materials, such as calcium and protein, and an imbalance in bone metabolism due to energy deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…D. Logical Relationship Structure (LRS) Logical Relationshil Structur (LRS) adalah hasil dari pemodelan ERD beserta attributnya sehingga bisa terlihat hubungan-hubungan antar entitas [10]. LRS dibentuk dengan nomor dari tipe record yang digambarkan oleh kotak persegi panjang dan dengan nama yang unik [11]. Penggambaran LRS mulai dengan menggunakan model yang dimengerti.…”
Section: Entity Relationship Diagram (Erd)unclassified
“…Exercise is known to have an important role in bone development 1 . There is also a known association between physical exercise and reduced bone resorption and bone formation, and exercise is consequently a strategy to reduce bone fragility and fracture risk, which are very common in childhood ¹.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a known association between physical exercise and reduced bone resorption and bone formation, and exercise is consequently a strategy to reduce bone fragility and fracture risk, which are very common in childhood ¹. Notable among clinical indicators of bone health are bone mineral content (BMC) and bone mineral density (BMD) 2 .…”
Section: Introductionmentioning
confidence: 99%